2014
DOI: 10.1371/journal.pone.0114263
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Whole Genome and Transcriptome Sequencing Reveals Diverse Transcriptomic Aberrations Driven by Somatic Genomic Changes in Liver Cancers

Abstract: Recent studies applying high-throughput sequencing technologies have identified several recurrently mutated genes and pathways in multiple cancer genomes. However, transcriptional consequences from these genomic alterations in cancer genome remain unclear. In this study, we performed integrated and comparative analyses of whole genomes and transcriptomes of 22 hepatitis B virus (HBV)-related hepatocellular carcinomas (HCCs) and their matched controls. Comparison of whole genome sequence (WGS) and RNA-Seq revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 39 publications
5
68
0
Order By: Relevance
“…A recent study also shows that the PBAF remodeling complex is important for doublestrand breaks (DSBs)-induced transcriptional silencing and promotes repair of a subset of DNA DSBs at early time points [48]. ARID2 has been recently identified as a key cancer gene for hepatocellular carcinoma [49,50], melanoma [51,52], and lung cancer [53]. Recently, a missense mutation R314C in ARID2 was reported in an individual with autism [54].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study also shows that the PBAF remodeling complex is important for doublestrand breaks (DSBs)-induced transcriptional silencing and promotes repair of a subset of DNA DSBs at early time points [48]. ARID2 has been recently identified as a key cancer gene for hepatocellular carcinoma [49,50], melanoma [51,52], and lung cancer [53]. Recently, a missense mutation R314C in ARID2 was reported in an individual with autism [54].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have described recurrent integration into the telomerase reverse transcriptase ( TERT ) and MLL4 genes accompanied by alteration in expression (likely driven by the Enhancer 2/Core promoter region of the integrated HBV DNA) [43,66,82,83,84,88,89]. Shiraishi et al showed that TERT and CDK15 contained integration breakpoints upstream of their respective transcriptional start sites, which generated fusion transcripts that were over-expressed [90].…”
Section: Hbv Dna Integrationmentioning
confidence: 99%
“…Recent studies reported that CDK14 is highly expressed in several malignant tumors, including HCC, taking part in the regulation of the cell cycle, tumor proliferation, migration, and invasion . Cyclin‐dependent kinase 15 was observed in an HBV–gene fusion in HCC and might participate in HBV‐driven transformation, which is an important risk factor of HCC . Expression of CDK16 is upregulated in HCC.…”
Section: Biology and Regulation Of Cdks In Hccmentioning
confidence: 99%